CO-MORBID DEPRESSION AND ALCOHOL USE DISORDER AMONG YOUTH LIVING WITH HIV ATTENDING A COMPREHENSIVE CARE CLINIC AT A PRIVATE HOSPITAL IN NAIROBI, KENYA - ABANJA WILLIAM OTIENO., (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2020)
BACKGROUND: Psychiatric morbidity has been associated with HIV disease since thebeginning of the AIDS epidemic. In youth with HIV infections alcohol use and depression makethe management more difficult and worsen the prognosis. Alcohol use also have adverseinteractions with the medications used hence reducing the effectiveness of the medications.Globally, depression is one of the leading causes of illness and disability among adolescents.Dispite this, minimal research has been done locally on the prevalence of various psychiatricmorbidities associated with HIV infection with none focusing on youth aged 15-24years old.STUDY OBJECTIVE: To determine the prevalence of depression and alcohol use disorderamong youth aged 15-24yrs under care for HIV & AIDS.DESIGN: Cross sectional analytical study design.STUDY SITE: Comprehensive Care Clinic (CCC) of Mater Misericordiae Hospital, NairobiKenya.METHOD: Survey method of HIV infected youth aged 15-24 yrs under CCC was used.Participants were given researcher designed questionnaire and subjected to both Alcohol UsueDisorder Inventory Test (AUDIT) and Beck’s Depression Inventory (BDI) which are selfadministered tests to a total of 194 participants. Analysis and presentation of results were doneusing statistical models and SPSS software.RESULTS: The prevalence of alcohol use disorder was 13% and the prevalence of depressionwas 77%. The sociodemographic factors that did not influence either or both alcohol use disorderand depression with a P-value above .05 were level of education, religion, residence and maritalstatus. Income, occupation, gender and age had a strong association with both alcohol usedisorder and depression at a P value of .000. The study also established an association betweenalcohol use disorder and depression at an Odd ration of 0.04.CONCLUSION: Youth with HIV/AIDS aged 15-24yrs receiving treatment still experienceconsiderable alcohol use disorder and depression. These youths can benefit from improveddelivery of psychiatric care adjunct to psychotherapy during follow up in CCC.RECOMMENDATION: In order to solve the twin problem of alcohol use and depressionamong HIV infected youth, key stakeholders need to design multidimensional strategies toeducate youth while creating impetus for them to avoid alcohol use and receive comprehensivescreening, diagnosis and treatment of depressive symptoms. It would be vital for preventivestrategies to be implemented in all CCC’s programes